Readers and writers in primary grades a balanced and integrated approach : K-4 - Combs, Martha (Upper Saddle River, N.J. Pearson/Merrill/Prentice Hall, 2006)
"Readers and Writers in Primary Grades is organized around strategies that benefit elementary school teachers in their efforts to be responsive to the developmental literacy needs of young children. Integrating theory and practice, these strategies offer a balanced look at appropriate literacy activities for K-3 classrooms. Chapter topics include reading aloud to children, shared reading, shared and interactive writing, guided and independent reading, guided and independent writing, literature study, developing phonological awareness and a strong phonics base, integrating phonics and structure, and linking children's learning experiences with a balanced literacy program."
Part I -- Literacy methods for K-4 classrooms -- Chapter 1. Foundations of language and literacy -- Chapter 2. Learning about words I : making the transition to print -- Chapter 3. Learning about words II : phonics and morphemic analysis -- Chapter 4. Reading aloud to children: foundations for comprehension of text -- Chapter 5. Shared reading: participating in a community of readers -- Chapter 6. Guided reading : scaffolding children's reading -- Chapter 7. Independent reading and reader's workshop : encouraging independence -- Chapter 8. Shared and interactive writing : participating in a community of writers -- Chapter 9. Guided and independent writing -- Part II -- Making connections : linking children's learning experiences within a balanced literacy programs -- Chapter 10. Teaching a basal reading / language arts series: integrating instruction to maximize children's learning -- Chapter 11. Integrating elements in a literacy framework: teaching about amphibians in second grade -- Appendix A. Handbook of children's literature -- Appendix B. Sample word lists and word sorts -- Appendix C. Pictures for sorting activities.
Rev. ed. of: Developing competent readers and writers in the primary grades. c1996.
Keywords: Language arts (Primary).; Reading (Primary).; English language -- Composition and exercises -- Study and teaching (Primary).; Language experience approach in education